2006
DOI: 10.1021/jp0616563
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Overall Water Splitting under Visible-Light Irradiation on (Ga1-xZnx)(N1-xOx) Dispersed with Rh−Cr Mixed-Oxide Nanoparticles:  Effect of Reaction Conditions on Photocatalytic Activity

Abstract: The photocatalytic activity of (Ga(1-x)Zn(x))(N(1-x)O(x)) loaded with Rh-Cr mixed-oxide (Rh(2-y)Cr(y)O3) nanoparticles for overall water splitting under visible-light irradiation (lambda > 400 nm) is investigated with respect to reaction pH and gas pressure. The photocatalytic performance of the catalyst is found to be strongly dependent on the pH of the reactant solution but largely independent of gas pressure. The present photocatalyst exhibits stable and high photocatalytic activity in an aqueous solution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(231 citation statements)
references
References 36 publications
12
217
2
Order By: Relevance
“…is useful for investigating whether a cocatalyst affects hydrogen or oxygen evolution sites. A good example is demonstrated for Rh 2-y Cr y O 3 cocatalysts on (Ga 1-x Zn x )(N 1-x O x ), as listed in Table 1 [49]. (Ga 1-x Zn x )(N 1-x O x ) without cocatalyst loading exhibited no activity for the photocatalytic HER, even in the presence of an electron donor (methanol).…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…is useful for investigating whether a cocatalyst affects hydrogen or oxygen evolution sites. A good example is demonstrated for Rh 2-y Cr y O 3 cocatalysts on (Ga 1-x Zn x )(N 1-x O x ), as listed in Table 1 [49]. (Ga 1-x Zn x )(N 1-x O x ) without cocatalyst loading exhibited no activity for the photocatalytic HER, even in the presence of an electron donor (methanol).…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionsmentioning
confidence: 99%
“…This experiment indicated that Rh 2-y Cr y O 3 functions as an efficient hydrogen evolution site. Another important feature of the Rh 2-y Cr y O 3 cocatalyst is its high selectivity for HER [49]. The water-splitting rate is significantly reduced in the presence of oxygen when RuO 2 is used as a cocatalyst because the photoreduction of oxygen competes with HER on RuO 2 .…”
Section: Electrocatalytic Hydrogen and Oxygen Evolution Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for the same base photocatalyst, the optimal pH depends on the co-catalyst due to hydrolysis and corrosion phenomena [156,160].…”
Section: Ph Of the Solutionmentioning
confidence: 99%
“…Several visible-light-driven photocatalyst materials loaded with cocatalysts such as Cr x Rh 2Àx O 3 /(Ga 1Àx Zn x )(N 1Àx O x ), Ru/SrTiO 3 :RhBiVO 4 , and graphitic carbon nitrides have been developed recently with a photocatalytic response at about 500 nm, but their quantum yields are still only a few percent. [34,[46][47][48] Photocatalytic hydrogen production by water splitting is an example of more general conversion processes that involve evolution of oxygen as one component and formation of chemical fuels as the other. An important example that is the focus of intense research is the photocatalytic reduction of carbon dioxide to methane, methanol, or ethanol.…”
Section: Solar Energy Conversionmentioning
confidence: 99%